The money shot : the Professional Athlete's Financial Playbook to Make the Big Time Last a Lifetime - Gifford, Crystal D. (Morgan James Publishing : Made available through hoopla, 2016)
The Money Shot provides a real look into the lives of a professional athlete and how this new-found fame and fortune can change their lives. Walking through the financial maze can be challenging for athletes who really need to focus on game performance. The tips and tools in the Money Shot allows athletes and their families to clearly identify how to find success in the money game so they can focus on career success as an athlete. Exploring the "do's" and "don'ts" of saving, spending, using, and growing money, the Money Shot is designed to provide the roadmap to successful financial performance by laying out the steps play-by-play. Athletes and their families gain knowledge to make the right moves for their financial present and future, and confidence to know they are performing at peak levels in the money game.